Using of opportunities of graphic processors for acceleration of scientific and technical calculations - Dudnik, V.A.; Kudrjavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2009)
The new opportunities of modern graphic processors (GPU) for acceleration of the scientific and technical calculations with the help of paralleling of a calculating task between the central processor and GPU are described. The description of using the technology NVIDIA CUDA for connection of parallel computing opportunities of GPU within the programme of the some intensive mathematical tasks is resulted. The examples of comparison of parameters of productivity in the process of these tasks' calculation without application of GPU and with use of opportunities NVIDIA CUDA for graphic processor GeForce 8800 are resulted. Описано нові можливості сучасних графічних процесорів (GPU) по прискоренню науково-технічних розрахунків за рахунок розпаралелювання обчислювального завдання між центральним процесором і GPU. Приведено опис використання технології NVIDIA CUDA для підключення паралельних обчислювальних можливостей GPU при програмуванні деяких математично інтенсивних завдань. Приведені приклади порівняння показників продуктивності при вирішенні цих завдань без застосування GPU і з використанням можливостей NVIDIA CUDA для графічного процесора GeForce® 8800. Описаны новые возможности современных графических процессоров (GPU) по ускорению научно-технических расчётов за счёт распараллеливания вычислительной задачи между центральным процессором и GPU. Приведено описание использования технологии NVIDIA CUDA для подключения параллельных вычислительных возможностей GPU при программировании некоторых математически интенсивных задач. Приведены примеры сравнения показателей производительности при решении этих задач без применения GPU и с использованием возможностей NVIDIA CUDA для графического процессора GeForce® 8800.